Penerapan Model Pembelajaran Problem-Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas VIII SMP Negeri 4 Satap Wori - Vikaldi Edwin Takaliwungan; Dientje F. Pendong; Femmy Kawuwung (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to analyze the application of the Problem-Based Learning (PBL) learning model in improving students' cognitive learning outcomes in science learning, especially in the material on the structure and function of plant tissues. The research was conducted at SMP Negeri 4 Satap Wori, with the research subjects in the form of 21 grade VIII students who had heterogeneous learning abilities. This study uses a class action research (PTK) approach in two cycles. In the first cycle, student learning outcomes showed that only 38.1% of students had completed, while 61.9% had not reached the Minimum Completeness Criteria (KKM). Based on the reflection of the first cycle, improvements were made in the second cycle by increasing student involvement, providing more motivation, and forming heterogeneous learning groups. The results in the second cycle showed a significant increase, with 85.7% of students achieving learning completeness in accordance with the KKM. The increase in learning completeness from the first cycle to the second cycle was 47.6%. This study concludes that the PBL model effectively improves students' critical thinking skills, creativity, and motivation and can help students solve problems independently and in groups. Therefore, applying the PBL model is recommended to continue to be used in learning that involves real-world problem-solving.